EFEKTIVITAS FUNGSI BADAN PERMUSYAWARATAN DESA (BPD) DALAM PENGAMBILAN KEBIJAKAN DI DESA KADUBALE KECAMATAN BANJAR KABUPATEN PANDEGLANG - Yunita Yunita; Gian Sumarna Gian Sumarna (NIAGARA Scientific Journal, 2021)
The Village Consultative Body (BPD) has a joint task with the Village Head to plan and establish policies for implementing governance and the physical development of the Village. The Village Consultative Body (BPD) is also a representative of the community, in this case it can participate in supervising the implementation of development and administration in the village. In addition, the Village Consultative Body (BPD) is also obliged to facilitate the implementation of the duties of the Village Head. The reality of the problems that occur in the field is the lack of effectiveness of the BPD function in Policy Making. To analyze the problems that occur the author uses the theoretical reference put forward by Gibson in Winardi (2011: 28). The law used in this study is Law number 6 of 2014 concerning village article 61. This research uses a qualitative method with a descriptive approach using data collection techniques by interview, observation and documentation. The results of the research conducted by the authors say that the effectiveness of the function of the Village Consultative Body (BPD) in policy making has not been effective. This is because the BPD does not yet know their respective duties and functions, the Kadubale Village Consultative Body does not play a role in carrying out its duties, in the preparation and discussion of village regulations, in agreeing on Kadubale village regulations, the BPD only follows the directions given by the village head.